The Prevalence and Risk Factors of Gastric Polyp in Endoscopy Unit at Prof. Dr. R.D. Kandou Hospital - Adiwinata, Randy; Andriani, Janette; Soetanto, Raynold; Waleleng, Andrew; Winarta, Jeanne; Rotty, Luciana; Gosal, Fandy; Tendean, Nelly; Waleleng, Bradley Jimmy (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Gastric polyps are usually asymptomatic; they are often incidentally discovered during an esophagogastroduodenoscopy (EGD) for other indication. Most of gastric polyps are benign, however, some have malignant potential. Therefore, identifying gastric polyp risk factors are crucial. This article aims to determine the prevalence and risk factor of gastric polyp in Endoscopy Unit at Prof. Dr. R.D. Kandou Hospital between April 2021-2022.Method: The retrospective study was using medical record data of all patients who underwent EGD between April 2021-2022. Data regarding patient’s characteristic, endoscopic finding, and risk factors were collected. Data was analyzed using SPSSv25.0 with Mann-Whitney, Chi-square-test, and logistic-regression.Results: There were 241 patients included, 56.4% were males. The median age was 53 years old. The most common symptom was epigastric pain (69.3%). The main indication of EGD was dyspepsia with alarm symptoms (79.25%). We found 24.1% of patients had gastric polyps. Most polyps were found in corpus (93.1%) and 70.7% were fundic gland polyp. We found that older age (p=0.001), female (p=0.003), gastritis (p=0.037), active-smoker (p=0.000), and one-year-PPI-usage (p=0.000) were significantly associated with gastric polyp. Logistic-regression analysis showed active smoking was the most significant risk factor (OR=9.3), followed by female gender (OR=6.4), and PPI-usage (OR=3.4). We found no significant association between esophagitis, bile-reflux, gastric ulcer, H. pylori infection, NSAID use, and alcohol abuse with gastric polyp.Conclusions: We found 24.1% gastric polyp prevalence with significant risk factors such as older age, female gender, gastritis, smoking, and long-term-PPI-usage.